Editing techniques: analysis on action scenes in road action films in Malaysia - Rosli Sareya; Zairul Anuar Md. Dawam; Humin Jusilin; Addley Bromeo Bianus (International Journal of Technical Research and Application (IJTRA), 2014)
This essay will dismantle about the utilization of editing techniques in an action scene in road action films in Malaysia. An action scene in films will look more dramatic and could provide optimum effect if appropriate editing techniques are used. It is not solely depending on the acting, visual and audio. However, editing techniques must be emphasized by the director and editor in producing a scene. The director and editor must be aware and know the suitability on the utilization of editing techniques in an action scene so that the desired effects could be achieved. Many researches have been conducted regarding the cinematography in films in Malaysia. Nonetheless, there is still a lack of emphasis on editing techniques. Thus, this article will focus on the editing techniques used through road action scenes by looking thoroughly on the suitability of their utilization in these road action scenes. Analysis is done by discussing into details based on the analysis method through continuous watching by viewing in stop motion, which is examining the pictures of each scene in the road action films in Malaysia, frame by frame.